Effects of squatting with elastic bands or conventional resistance - training equipment at different effort levels in post-exercise intraocular pressure of healthy men - Gene-Morales, Javier; Gené-Sampedro, Andrés; Salvador-Palmer, Rosario; C. Colado, Juan (Biology of Sport, 2022)
This study aimed to compare intraocular pressure (IOP), mean ocular perfusion pressure (MOPP) and central corneal thickness (CCT) acute adaptations to squat exercise using elastic bands (EB) or weight plates (WP) together with the weight of the bar and applying maximal or submaximal efforts. Cardiovascular parameters (pulse pressure, mean blood pressure, heart rate), rate of perceived exertion, kilograms, and number of repetitions served to monitor psychophysiological acute variations. Twenty physically active males (25.55 ± 4.75 y.o.) underwent two sessions (one for familiarization and one for the experimental trial). In the experimental session, ocular and cardiovascular pre-exercise measurements were taken. Then, two sets using WP and two using EB attached to the bar with the same load were performed by each subject in random order. Immediately after finishing each set, the subjects rated perceived exertion, and cardiovascular and ocular measurements were taken,in this order. An ANOVA with post-hoc LSD evaluated differences between sets. IOP significantly decreased (p < 0.001, ƞp² = 0.513), and MOPP (p 0.05). EB permitted more repetitions to be performed and led to non-significantly lower post-exercise IOP values (effect size [d] compared to resting 0.79 and 1.00) in comparison to WP (d = 0.73–0.74). IOP and ocular and systemic hemodynamic responses are similar when using EB instead of WP to load the bar, with EB allowing a larger number of repetitions. Data presented in this paper may help with the prescription of resistance training for people with glaucoma risk factors.